Social Values on the Novel "Aku Harus Jadi Malaikat" Zakiah D Aziz's Work : Review of Literature Sociology and the Relevance as Teaching Material in Senior High School - Dewi Handayani; Oky Fardian Gafari; Wisma Hadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The aim of this journal is to research the social values on the Novel “Aku Harus Jadi Malaikat” was witten by Zakiah D Aziz’s as teaching material in Senior High School. The methodology research is a qualitative research, but the preparation process is assisted by quantitative research. In qualitative research of instrument is the researcher himself and the method used is descriptive qualitative method, this method is used to analyze, describe and describe the elements that become the center of research. The result is this study can be implemented as teaching materials in novel texts. As well as introducing an author's perspective in writing his work. By paying attention to structures such as themes, characters / characterizations, paths, settings and mandates, so that they can be more easily understood by students.